Comparison of clinical and radiographic severity of juvenile-onset versus adult-onset ankylosing spondylitis. Issue 9 (9th September 2008) - O'Shea, F D; Boyle, E; Riarh, R; Tse, S M; Laxer, R M; Inman, R D
Abstract : Objectives: An important unresolved issue in the pathogenesis and clinical course of ankylosing spondylitis (AS) is whether juvenile-onset AS (JoAS) is a clinical entity in its own right or just an earlier onset variant of adult-onset AS (AoAS). A study was undertaken to address this issue. Methods: All patients with AS were extracted from the database of a large spondylitis clinic. Those with symptom onset at ⩽16 years were compared with those with symptom onset at ⩾17 years. Odds ratios (OR) were calculated and adjusted for disease duration and current age. Results: 267 patients with AS were identified; 84 met the criteria for JoAS and 183 met the criteria for AoAS. There were no differences in gender ratio (male: JoAS 81%, AoAS 79%) or in HLA-B27 status (positive: JoAS 75%, AoAS 81%). The axial/peripheral pattern of disease at presentation differed; an exclusively peripheral pattern was seen in 26% with JoAS but in only 4.6% of those with AoAS (p<0.001). There were no differences in disease activity between the two groups. When adjusted for disease duration, axial features were more prominent in AoAS than JoAS as represented by neck pain (OR 2.93 (95% CI 1.54 to 5.55)), neck stiffness (OR 3.39 (95% CI 1.80 to 6.39)), back pain (OR 2.96 (95% CI 1.43 to 6.11)) or back stiffness (OR 3.30 (95% CI 1.50 to 7.28)). AoAS was associated with worse functional and quality of life measures and higher fatigue scores when adjusted for disease duration. Conclusions: JoAS follows a distinctive clinical course from AoAS. These clinical features are dictated by factors other than male gender and HLA-B27 and warrant further investigation.